Leadership and the art of struggle how great leaders grow through challenge and adversity - Snyder, Steven (Berrett-Koehler, 2013)
Leadership is often a struggle, and yet strong taboos keep us from talking openly and honestly about our difficulties for fear of looking weak and seeming to lack confidence. But Steven Snyder shows that this discussion is vital-adversity is precisely what unlocks our greatest potential. Using real-life stories drawn from his extensive research studying 151 diverse episodes of leadership struggle-as well as from his experiences working with Bill Gates in the early years of Microsoft and as a CEO and executive coach-Snyder shows how to navigate intense challenges to achieve personal growth and organizational success. He details strategies for embracing struggle and offers a host of unique tools and hands-on practices to help you implement them. By mastering the art of struggle, you'll be better equipped to meet life's challenges and focus on what matters most.